CFD analysis of effect of flow and geometry parameters on thrust force created by flow from nozzle - Pathan, Khizer Ahmed; Khan, Sher Afghan; Dabeer, P. S. (IEEE, 2017)
This paper presents the Computational Fluid Dynamic (CFD) analysis to study the effect geometry and flow parameters on thrust force created by the flow from convergent divergent nozzles to a suddenly expanded circular duct of larger cross-sectional area. The study is focusing on resultant thrust force. The nozzles are designed for Mach numbers 1.1, 1.4, 1.8 and 2.0. The CFD analysis is done by varying the area ratios and nozzle pressure ratios for all Mach numbers. The area ratios considered for the analysis are 1, 2, 4, 6, 8, 10 and 12. The values of nozzle pressure ratios considered in the analysis are 2, 4, 6, 8, 10 and 12. The results for different combinations of Mach number, area ratios and nozzle pressure ratios are compared with the help of tables. By observing all the results it can be concluded that the resultant thrust force created by flow through nozzle is strongly influenced by Mach number, area ratio and Nozzle pressure ratio.